The Role of the Entrepreneurship Mindset and Spirit in Building a Tourism Business in Indonesia Post COVID-19 - FIRDAUS, Adhy; NORVADEWI, Norvadewi; MURYANTI, Muryanti; HIDAYATULLAH, Syarif; SAKSANA, Joned Ceilendra; SITORUS, Sunday Ade (Journal of Environmental Management and Tourism, 2022)
The purpose of this research is to know and analyze directly or indirectly the entrepreneurial mindset and spirit have a significant effect on increasing business performance through self-motivation of entrepreneurs in rebuilding tourism businesses after COVID-19. This study examines the variables related to the entrepreneurial mindset and spirit, while the dependent variable is increasing business performance through moderating variables, namely self-motivation of entrepreneurs in rebuilding tourism businesses after COVID-19. The research method used in this research is descriptive quantitative research method using path analysis. In this study the independent variable is related to mindset and entrepreneurial spirit while for the dependent variable, namely the variable business performance improvement and the moderator variable is the variable self-motivation from entrepreneurs in rebuilding tourism businesses post-covid-19, data analysis using AMOS 18 and the data taken is data on the number of entrepreneurs in the Indonesian tourism industry in 2016-2020. Partially, the variables of mindset and entrepreneurial spirit have a significant effect on the variables of increasing business performance and self-motivation. Simultaneously, the variables of mindset and entrepreneurial spirit have an effect on the variable of increasing business performance through self-motivation variables. Through the results of research that has been stated that with a good mindset in carrying out the business that will be built by thinking about what business concepts will be developed after being slumped by COVID-19, plus increasing the spirit of entrepreneurship will improve performance in business for entrepreneurs in the tourism industry, increasing Performance is due to an increase in self-motivation in carrying out and turning his business into a successful business.